The Differences of Night Eating Syndrome, Sleeping Pattern, and Sugar-Sweetened Beverage Consumption Habit based on Metholic Type in Obese Students (London Journal of Medical and Health Research, 2025)
Background: The prevalence of obesity in students is currently increasing and it can lead to  metabolic syndrome at such a young age. The habit of students who have bad sleeping pattern, night  eating syndrome, and excessive SSB consumption can increase the risk of metabolic syndrome in  obese students. Purpose: The purpose of this research was to analyze the differences of night eating syndrome,  sleeping pattern, and consumption habit of sugar-sweetened beverage based on metabolic types in  obese students. Method: The research was conducted in July-September 2020 with female students in Semarang  City as subjects. This research used a case-control design, as many as 52 subjects aged 19-24 years  were selected by consecutive sampling method. The collected data included: body weight using  digital scales, height using a microtoise, waist size using a medline, blood pressure using a  tensimeter, and a laboratory tests was conducted to check triglyceride levels, HDL cholesterol,  fasting blood glucose, as well as insulin. The used instruments were The Night Eating Questioner  (NEQ) to assess the night eating syndrome, Pittsburg Sleep Quality (PSQI) to assess sleeping  pattern, and Semi-Quantitative Food Frequency Questionnaire (SQFFQ) to see the subject’s  consumption of sugar-sweetened beverage during the last one month. The data were analyzed using  Chi-Square test. Result: The research showed that majority of the subjects who experienced night eating syndrome  (46,2%) and bad sleeping pattern (61,5%) were subjects with Metabolically Unhealthy Obesity  (MUO). Meanwhile, for sugar-sweetened beverage consumption in Metabolically Healthy Obesity  (MHO) and Metabolically Unhealthy Obesity (MUO) were still within the normal range (86,4%). A  difference between night eating syndrome (p=0,006) and sleeping pattern (p=0,012) on  Metabolically Healthy Obesity (MHO) and Metabolically Unhealthy Obesity (MUO) was also  observed. Conclusion: Students with Metabolically Unhealthy Obesity (MUO) type were experiencing more  night eating syndrome and bad sleeping pattern compared to the students with Metabolically Healthy  Obesity (MHO) type.
Keywords: Depression; antidepressants; pharmaceutical industry; psychiatric drug research; guillain barre syndrome; Chikungunya; Peripheral neuropathies; Arboviruses.; Tibial plateau fracture; anterior cruciate ligament injury; arthroscopic surgery; ligament reconstruction; Metabolically Healthy Obese (MHO); Metabolically Unhealthy Obese (MUO); Night Eating Syndrome; Sleep Pattern; Sugar-Sweetened Beverage.